Criticism of Empiricism in Edmund Husserl’s works “Logical Investigations”, “Philosophy as Rigorous Science” and “Prima Philosophia” - Kebuladze, Vakhtang (Sententiae, 2011)
The paper deals with the phenomenological criticism of empiricism. The author compares these two philosophical conceptions showing their similarity and their differences. Both phenomenology and empiricism are philosophies of experience; however, phenomenological analysis of empiricism reveals some of empiricism’s fundamental mistakes: 1. Empiricism is incapable to distinguish empirical and transcendental self-experience (Selbsterfahrung). 2. Empiricism fails to grasp the intentional character of consciousness. 3. Empiricism «doesn’t see the ideas». 4. Empiricism identifies contemplation with contemplation of the singular. Together with Husserl the author criticizes psychologism and naturalism and analyses empiric concepts of association and induction. He shows that, contrary to empiricism’s claims, association is not only passive but also active, and induction isn’t sufficient for creation of general notions.